"Candidatus Euplotechlamydia quinta, " a novel chlamydia‐like bacterium hosted by the ciliate Euplotes octocarinatus (Ciliophora, Spirotrichea). (11th September 2022) - Wang, Ruanlin; Sun, Ruijuan; Zhang, Zhiyun; Vannini, Claudia; Di Giuseppe, Graziano; Liang, Aihua
Abstract: Our knowledge of ciliate endosymbiont diversity greatly expanded over the past decades due to the development of characterization methods for uncultivable bacteria. Chlamydia‐like bacteria have been described as symbionts of free‐living amoebae and other phylogenetically diverse eukaryotic hosts. In the present work, a systematic survey of the bacterial diversity associated with the ciliate Euplotes octocarinatus strain Zam5b‐1 was performed, using metagenomic screening as well as classical full‐cycle rRNA approach, and a novel chlamydial symbiont was characterized. The metagenomic screening revealed 16S rRNA gene sequences from Polynucleobacter necessarius, three previously reported accessory symbionts, and a novel chlamydia‐like bacterium. Following the full‐cycle rRNA approach, we obtained the full‐length 16S rRNA gene sequence of this chlamydia‐like bacterium and developed probes for diagnostic fluorescence in situ hybridizations. The phylogenetic analysis of the 16S rRNA gene sequences unambiguously places the new bacterium in the family Rhabdochlamydiaceae . This is the first report of chlamydia‐like bacterium being found in Euplotes . Based on the obtained data, the bacterium is proposed as a new candidate genus and species: " Candidatus Euplotechlamydia quinta."